Roles of Antimony and Molybdenum Additions in Mn–Sn–W–O/IrO2–SnO2–Sb2O5/Ti Anodes for Oxygen Evolution in Seawater Electrolysis - Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
An attempt was made to enhance the oxygen evolution efficiency in seawater electrolysis by additions of antimony and molybdenum to manganese–tin–tungsten oxide electrocatalyst prepared by anodic deposition on the intermediate Ir1–x–ySnxSbyO2+0.5y/Ti electrode. Ir1–x–ySnxSbyO2+0.5y/Ti supported nanocrystalline g–MnO2 type Mn–Sn–W–X(X=Sb or/and Mo)–O electrocatalysts with grain size of about 4-8 nm were tailored by anodic deposition and these anodes showed almost 100 % oxygen evolution efficiency at current density of 1000 A.m-2 in 0.5 M NaCl solution of pH 1 at 25°C. They guaranteed the stable anode performance of 99.60-99.85% oxygen evolution efficiency for more than 5 months at current density of 1000 A.m-2 in 0.5 M NaCl solution of pH 1 at 25°C. Keywords: Oxygen evolution anodes, electrocatalyst, CO2 recycle, XRD, SCLM. DOI: 10.3126/jncs.v25i0.3277 Journal of Nepal Chemical Society Volume 25, 2010 pp 9-18